Aerosol transport in a bifurcating tube at cyclic flow - Miguel, A. F. (2016)
Branching tube flow is a common feature of many fields of science and technology, and occurs both in animate and inanimate systems [1]. The transport of aerosol particles is of particular importance in industrial flow networks but also for the respiratory tree [2]. In this analysis a 3-D numerical study is performed to investigate transport and deposition of aerosol particles in branching tubes. Bifurcation tubes designed according to Hess-Murray law [3] but with different branching angles are analyzed. This study covers cyclic flow conditions at frequencies of 0.25 Hz, 0.50 Hz and 0.75 Hz, Stokes numbers ranging between 0.03 and 0.25, and Reynolds numbers up to 3000.